Positive correlation between fasting plasma glucagon and serum C-peptide in Japanese patients with diabetes - Hosokawa, Yoshiya (Heliyon, 2019)
AIMS: Glucagon plays pivotal roles in systemic glucose homeostasis mainly by promoting hepatic glucose output. Using a sandwich enzyme-linked immunosorbent assay (ELISA), we evaluated fasting plasma glucagon levels in hospitalized patients with type 1 or type 2 diabetes, and assessed the relationships between glucagon levels and various clinical parameters. METHODS: We enrolled adult Japanese diabetes patients admitted to Osaka University Medical Hospital for glycemic control between July 2017 and May 2018 in this study. After patients had fasted for 12 h, blood samples were obtained and plasma glucagon levels were measured using a sandwich ELISA. RESULTS: Total 107 patients participated in the study. The mean fasting plasma glucagon level of patients with acute onset type 1 diabetes was significantly lower than that of patients with type 2 diabetes (p < 0.05). Plasma glucagon levels were not significantly correlated with plasma glucose levels in patients with type 1 diabetes or in patients with type 2 diabetes. Multiple regression analysis indicated that fasting glucagon levels were independently and significantly correlated with fasting serum C-peptide levels in patients with type 2 diabetes. CONCLUSIONS: Our results suggest that insulin and glucagon secretion are balanced in the fasting state in patients with type 2 diabetes.